KENDAL CITY BRANDING - Dwi Ismiati; Anung Rachman; Aris Setiawan (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
In 2021, Kendal district launched the city branding program through Kendal Handal